The Patient-Centered Care and Receipt of Preventive Services Among Older Adults With Chronic Diseases: A Nationwide Cross-sectional Study - Hailun Liang DrPH; Junya Zhu PhD; Xiangrong Kong PhD; May A. Beydoun PhD, MPH; Jennifer A. Wenzel PhD, RN, CCM, FAAN; Leiyu Shi DrPH, MBA, MPA (SAGE Publishing, 2017)
This article investigates the associations between the patient-centered care (PCC) and receipt of preventive services among older adults with chronic diseases. Data were derived from the nationally representative Medical Expenditure Panel Survey. The full-year consolidated data files from 2009 to 2013 were pooled to yield a final analytic sample (N = 16 654). Study outcomes included the receipt of 7 types of preventive screenings and 2 types of health education services. Patients' PCC groups were categorized as PCC, partial PCC, and non-PCC, based on 9 questions classified under the 3 distinctive attributes of PCC-whole-person care, patient engagement, and enhanced access to care. Prevalence rates for each outcome variable were calculated. We estimated odds ratios from multiple logistic regressions, comparing the likelihood of outcome variables across 3 groups of patients. Adjusting for covariates, the PCC group was more likely than the non-PCC group to receive 8 types of preventive services. The partial PCC group had a greater likelihood than the non-PCC group of receiving 7 types of preventive services. Our study reveals significant associations between PCC and receipt of preventive services. PCC has demonstrated the potential to improve preventive care for older adults with chronic diseases.